Irregular menstrual cycles as a risk factor of type 2 diabetes mellitus in women of childbearing age - Dhea Aghestya; Nurmasari Widyastuti; Martha Ardiaria; Fillah Fithra Dieny (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background: Irregular menstrual cycles are a risk factor for developing type 2 diabetes mellitus (DM) in women. Objective: This study aimed to evaluate irregular menstrual cycles as a risk factor of type 2 DM in women of childbearing age with body fat percentage, waist-hip ratio, diet quality, and physical activity as confounding factors.Methods: This was a case-control study. Its subjects were subjects with type 2 diabetes mellitus (n=31) and subjects without any clinical evidence of abnormal glucose regulation (n=31) who attended Puskesmas (Community Health Centre) Rowosari, Tembalang, Semarang with over 30 years of age. Based on their menstrual cycles, they were divided into two groups: women with irregular menstrual cycles, and those with regular menstrual cycles. Cochran Mantel-Haenszel test was used to control their confounding factors. Results: There was an association between irregular menstrual cycles and type 2 DM (p<0.05) with a 7.2 greater risk on women of childbearing age (OR = 7.2, 95% CI=2.18-23.75). By the Cochran Mantel-Haenszel test, the association was still significant; women with over percentage of body fat and central obese with irregular menstrual cycle had 4,85 times and 4,37 times of sequentially greater risk on type 2 DM (OR = 4.85, 95% CI=0.98-23.95 vs OR = 4.37, 95% CI=0.93-20.51).Conclusion: The irregular menstrual cycles was a risk factor of type 2 DM, especially in obese women of childbearing age.